Time Window of the Critical Period for Neuroplasticity in S1, V1, and A1 Sensory Areas of Small Rodents: A Systematic Review - Pedrosa, Laís Resque Russo; Coimbra, Gabriele dos Santos; Corrêa, Márcio Gonçalves; Dias, Ivanira Amaral; Bahia, Carlomagno Pacheco (Frontiers in Neuroanatomy, 2022)
The plasticity of the central nervous system (CNS) allows the change of neuronal organization and function after environmental stimuli or adaptation after sensory deprivation. The so-called critical period (CP) for neuroplasticity is the time window when each sensory brain region is more sensitive to changes and adaptations. This time window is usually different for each primary sensory area: somatosensory (S1), visual (V1) and auditory (A1). Several intrinsic mechanisms are also involved in the start and end of the CP for neuroplasticity; however, which is its duration in S1, VI, and A1? This systematic review evaluated studies on the determination of these time windows in small rodents. The careful studies selection and methodological quality assessment indicated that the CP for neuroplasticity is different among the sensory areas and the brain maps are influenced by environmental stimuli. Moreover, there is an overlap among the time windows of some sensory areas. Finally, the time window duration of the CP for neuroplasticity is predominant in S1.